Perancangan Infografik sebagai Media Pendukung Sosialisasi KPU ke Daerah Terpencil - Putra, M. Edo Pratama (Besaung : Jurnal Seni Desain dan Budaya)
The General Election was held in 2019 with the KPU as the organizer on April 17, 2019. Among the tasks of the KPU was the dissemination of General Elections to remote areas throughout Indonesia. Remote areas are the main concern of the KPU in an effort to increase election participation in 2019, because remote areas are one of the biggest contributors to the Golput number in the 2014 elections. One of the remote areas with very low participation rates is Tegal Rejo Village, Gedang Sari District, Gunung Kidul Regency. This village is located in a hilly area which is one of the disaster prone areas. Tegal Rejo village has not received socialization from the Gunung Kidul Regency KPU and many villagers are still not informed about the 2019 Presidential Election. From the problems that occur, the author finds a solution to the problem by making an "Infographic Design as a Media Supporting the Socialization of KPU to Remote Areas". As for this design contains information on Election 2019, such as the introduction of candidates in the form of profiles of each prospective president and vice president, procedures for voting, time and place of execution until the conditions become a Permanent Voters List (DPT). And the media created will be given to the KPU to be the material for dissemination to remote areas in Indonesia.